2021
DOI: 10.32734/jomas.v1i3.6984
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stakeholder Perception on Transparency, Accountability And Effectivity In School Operational Assistance Funds Management For Junior High School Level In North Aceh Regency

Abstract: This study aims to analyze the differences in perceptions of internal stakeholders and external stakeholders about transparency, accountability and effectivity in the management of School Operational Assistance (BOS) funds in 97 State junior high schools in North Aceh Regency. The sample in this study is divided into two groups, they are the internal stakeholders group who is consisting of 97 principals, 97 vice principals, 97 treasurers and 97 committee chairs which is obtained by the saturated sample method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…The better the level of quality of the procurement committee, the quality of goods/services providers, procurement systems and procedures, and risk assessment, the less fraud in the procurement of goods/services (Nurharjanti, 2017). These results are in line with Dahliana et al (2021) found that the accountability of BOS funds in the procurement of goods/services is better with good governance and can be documented with the SIPLah mechanism. Darmawan & Wardhono (2023) provide evidence that the implementation of goods/services procurement policies through the SIPLah implementation can help manage BOS funds for the procurement of goods and services more transparently, effectively, and efficiently.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…The better the level of quality of the procurement committee, the quality of goods/services providers, procurement systems and procedures, and risk assessment, the less fraud in the procurement of goods/services (Nurharjanti, 2017). These results are in line with Dahliana et al (2021) found that the accountability of BOS funds in the procurement of goods/services is better with good governance and can be documented with the SIPLah mechanism. Darmawan & Wardhono (2023) provide evidence that the implementation of goods/services procurement policies through the SIPLah implementation can help manage BOS funds for the procurement of goods and services more transparently, effectively, and efficiently.…”
Section: Introductionsupporting
confidence: 70%
“…Efforts to realize transparency can be made by involving stakeholder components, in this case, guardians or parents of students, and school committees in the preparation of the School Activity and Budget Plan (RKAS) (Dahliana et al, 2021). Mutangili (2019)provides evidence that goods and services procurement activities where every process is carried out transparently, such as in the process of selecting goods and services providers, make it possible to mitigate fraudulent practices in the procurement cycle.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Perencanaan pemerintah dalam menggalakan kewajiban belajar 9 (sembilan) tahun di dukung oleh dengan adanya Bantuan Operasional Sekolah (BOS) yang diberikan pemerintah kepada setiap sekolah (Fitriah, A., Sumintono, B., Subekti, N. B., & Hassan, 2013); (Dahliana, N. A., & Khaddafi, 2021), dengan begitu diharapkan semua warga Indonesia dapat mengenyam pendidikan tanpa khawatir dengan biaya yang dibebankan dan memiliki kualitas warga negara yang baik secara pengetahuan dan kempuan mengelola hidup yang lebih baik.…”
Section: Pendahuluanunclassified
“…Apart from that, the role of leadership is very crucial (Maruapey et al, 2023;Niswaty et al, 2019;Rifdan et al, 2022), so that leadership involvement can influence the continuity of school operational assistance funds which are carried out well (Dahliana et al, 2021;Hidayat et al, 2019;Ngaba, 2017). So it will become a legal framework for implementing financial governance which can increase accountability in fund management.…”
Section: Introductionmentioning
confidence: 99%